Growth of straight carbon nanotubes by simple thermal chemical vapor deposition - 邹小平 H. ABE T. SHIMIZU A. ANDO H. TOKUMOTO 朱申敏 周豪慎 (Transactions of Nonferrous Metals Society of China, 2006)
Straight carbon nanotubes （CNTs） were achieved by simple thermal chemical vapor deposition（STCVD） catalyzed by Mo-Fe alloy catalyst on silica supporting substrate at 700 ℃. High-resolution transmission electron microscopy images show that the straight CNTs are well graphitized with no attached amorphous carbon. Mo-Fe alloy catalyst particles play a very crucial role in the growth of straight CNTs. The straight carbon nanotubes contain much less defects than the curved nanotubes and might have potential applications for nanoelectrical devices in the future. The simple synthesis of straight CNTs may have benefit for large-scale productions.